Exploring the 21st century ESL learning strategies of students in Malaysia's higher technical institute - Ab Rahman, Faizahani; Yahya, Yasir; Majid, Sheikha; Ahmad, Ajhar (UUM Press, Universiti Utara Malaysia, 2021)
This research was conducted at a private technical institute of higher learning to explore the different 21st century language learning strategies used by proficient and low proficient ESL learners. In conducting the study, the range of language learning strategies was identified and the frequency of these strategies were recorded. This research determines the choice of in and out of class language learning strategies of learners by the different language performance and academic background of their parents. Using questionnaire adopted from various researchers, 241 respondents who were students of the second, third, fourth or fifth semester from a private technical institute who have just completed the course were used and then analysed using SPSS. The research findings reveal that there were 7 dimensions of the 21st century language learning strategies showing high correlation at p=0.05. The dimension which recorded the strongest correlation with strategy is to get online assistance at 0.962. The findings with 10 highly proficient and 10 low proficient learners indicated there are 46 language learning strategies with 22 strategies being frequently used by the more proficient language learners.